The impact of multipurpose dams on the values of nature’s contributions to people under a water-energy-food nexus framing - Foudi , S.; McCartney, Matthew P.; Markandya, A.; Pascual, U. (Elsevier, 2023)
The paper proposes a probabilistic approach to the assessment of the impacts of multipurpose dams. It is framed around the notion of Nature’s Contributions to People (NCP) in the setting of the Water-Energy-Food nexus. The socio-ecological context of the Tana River Basin in Kenya and the construction of two multipurpose dams are used to highlight co-produced positive and negative NCP under alternative river regimes. These regimes produce both damaging floods that ought to be controlled and beneficial floods that ought to be allowed. But the river regime that results from hydropower generation and flood risk reduction may not be the one that is most conducive to food and feed-based NCP. The approach relates the economic value of river-based NCP coproduction to the probability of flooding to derive the expected annual value of NCP and a NCP value-probability curve. The relation between NCP flows and flood characteristics is tested and estimated based on regression analyses with historical data. Results indicate that the net economic value of key NCP associated with multipurpose dams for local people and associated social equity effects largely depend on the frequency of flood events and on the way impacts are distributed across communities, economic sectors and time.